SAB’ATU AHRUF DAN KONTRIBUSINYA DALAM PENGEMBANGAN ILMU AL-QUR’AN - Halimatus Adiah; Rika Afrida Yanti; Irwansyah (LPPM-IAI BATAM, 2022)
Al-Qur'an was revealed with Sab'atu ahruf or in its harfiyah it means Al-Qur'an was revealed with seven letters. And this is one of the important studies to comprehend the substance and essence contained in the Qur'an in a comprehensive manner. However, the scholars di(ffered in the meaning of the sab'atu ahruf. In fact, the difference of opinion among the scholars was almost forty differences of opinion. This, of course, caused controversy both among Muslims as well as among Orientalists. From these differences, the orientalists made arguments among them to debate the authenticity of the Al-Quran as the holy book that comes from Allah SWT. Apart from that, the Islamic ummah also has questions regarding the meaning of the sab'atu ahruf. Why are there differences of opinion that are quite contrasting in interpreting it, and what is the true meaning of the sab'atu ahruf. Departing from this description, this paper will focus on seeing the meaning and substance of the sab'atu ahruf. And we will also see how the urgency of the existence of this sab'atu ahruf is to enrich the knowledge of understanding and interpreting the content and substance contained in the Al-Qur'an, from the side of the meaning of sab'atu ahruf. The method used is by referring to a review of books or literature as data collection materials and analysis tools used in completing this writing.